(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The sustainability of processing foods towards consumers’ buying decisions this year with the advent of modern technology, capitalists can produce more and more products. Over the years, consumers have changed their decisions based on their wants and needs, especially today’s people. The research came up during a time that was not convenient for the products because of the low quality of technology or mechanical used in making the products and consequently also a low supply of the product that will cause a shortage of supply. Therefore, this study used a descriptive research method of design. The study’s respondents were thirty (30) selected processing company employees. This study utilized a purposive sampling technique. Data were tallied and analyzed using frequency, percentage, and weighted mean. Therefore, in addition to that, respondents said that the company also assures its trade partners of delivering fresh, clean, and safe stocks at all times, adhering to the standards of good manufacturing practices and standard sanitation operating procedures. Based on the data gathered on the sustainability of processing foods towards customers’ buying decisions on Processing foods in terms of Product innovation, quality control, standard procedure, and machinery and equipment. Product innovation got 4.23, which is Very highly Sustainable. At the same time, the quality control was highly sustainable, got 3.77, while the standard procedure Perform set up and clear up instruction got 4.33 and was interpreted as very highly sustainable, and machinery and equipment awareness of the safety of machinery got 3.87, and interpreted as highly sustainable. Therefore, customers’ buying decisions regarding product innovation, quality control, standard procedure, machinery, and equipment are highly sustainable to give the best quality in every product. Hence, the customer is satisfied with the product they sell. Low and fair pricing of products are some of the wants or needs of every customer buying a product. To maintain the quality and price of their goods while providing for the customer’s satisfaction, they must be knowledgeable about the product, know its benefits Always maintain the quality of the product and cleanliness of the store so that the consumers have solid relationships and are satisfied with the product in purchasing decisions.